Desarrollo clínico-biológico de ratas alimentadas con dieta semi-purificada a base de clara de huevo - González-Infante, Gabriela Alejandra (2021)
There is a shortage of concentrated feeds for animals in the country and therefore the research focused on developing a diet based on the guidelines of the American Institute of Nutrition (AIN) with endogenous ingredients and testing them in rats in pregnancy, lactation and growth. In Experiment 1, 12 male Sprague Dawley (SD) rats of 5-6 weeks were worked, half of them fed with a control diet and the other half with a non-purified diet based on egg white (EWP) for six weeks. In Experiment 2, 10 pregnant SD rats were subjected to the same diets (control and EWP) to select 14 four-week-old male neonates to continue with the same feeding regimens for five more weeks (7 in control diet and 7 in EWP). In both experiments, an evaluation of clinical-metabolic parameters (body weight, clinical evaluation and metabolic cage study) was carried out. In the second experiment, biological parameters (protein concentration and hematology) were also evaluated. The results show stable clinical-metabolic parameters and normal biological parameters, which allows to conclude that EWP is suitable for the optimal and healthy development of laboratory rats.